Flood frequency analysis of annual maximum stream flows using l-moments and tl-moments approach - Ahmad, Ummi Nadiah (Springer New York, 2011)
Flood frequency analysis (FFA) is the estimation of how often a specified event will occur. Before the estimation can be done, analyzing the stream flows data are important in order to obtain the probability distribution of flood. By knowing the probability distribution, prediction of flood events and their characteristics can be determined. The aim of this study is to perform the FFA of annual maximum stream flows over station in Negeri Sembilan, Malaysia by using the L-Moments (LMOM) and TL-Moments with trimming only one smallest value (TLMOM1) approach. The most suitable distribution was determined by the use of MADI and moments ratio diagram. The result shows that GLO distribution to be the best distribution fitted the data of annual maximum stream flows for stations in Negeri Sembilan, Malaysia.